Enhancing ICT Facilities in Secondary Mathematics Education: A Literature Review - Onesme Niyibizi (Journal of Technology-Assisted Learning, 2025)
This systematic review synthesizes findings from 43 past studies to examine the challenges and effectiveness of integrating Information and Communication Technology facilities into secondary school mathematics instruction. The primary objective was to analyze ICT’s potential to enhance the teaching and learning of mathematical concepts. Studies were selected based on publication date, relevance to secondary school mathematics, and focus on both the benefits and challenges of ICT integration. The review revealed significant benefits of ICT, including increased student motivation and improved communication. However, it also underscored that the effectiveness of ICT integration is highly dependent on implementation and support within the teaching environment. A detailed analysis of the selected literature highlighted common themes and barriers teachers face when incorporating ICT. Results indicated that while ICT tools enhance mathematical learning, successful integration linkages on factors such as teacher training, adequate infrastructure, and the ability to adapt ICT to the existing curriculum. Furthermore, the review identified a notable gap in research concerning the challenges teachers face. This suggests a critical need for future studies to investigate deeper into these obstacles. This analysis stresses the imperative for more research into the barriers to effective ICT implementation in secondary school mathematics education. Despite the documented advantages of ICT in teaching, there is a clear gap in understanding the challenges teachers encounter. Future research should not only focus on the benefits of ICT but also on strategies to overcome these obstacles, ultimately ensuring successful ICT integration to enhance teaching outcomes and student engagement in mathematics education.